Transcendência da morte em idosos: histórias plurirreligiosas de resiliência em busca da plenitude. - Gomes, Maria Suênia de Medeiros (2021)
The present work was developed intent on comprehending, with a systemic look, how religion/spirituality contributes in the process of the elderlies’ resilience as a tool of protection on dealing with existential suffering, by discussing whether it foments support to face death, defend the environment, avoid suicide, exacerbated consumerism, alongside the fact that it may soften the physical and mental impact caused by the Covid-19 syndrome, and lead to reflecting over the meaning of life and researching into new ways of promoting a dignified aging process. Hence, the theme development was structured in 3 (three) basic axes, as follows: aging; resilience; and death. As from that, it was sought to investigate, in the scientific field, theoretical fundamentals which embraced the aforementioned themes by collecting, in relation to the aging theme, studies presented by Beauvoir, Boff, Bauman, Fromm, Grun, Han, Honoré, and Foucault. The resilience theme axis was researched in works by Berger, Cyrulnick, Campbell, Grotberg, Henriqueta Camarotti, Lenoir, Frankl, Jung, Meslin, Pope Francis, Scheler, Teixeira, Passos, and Usarski. With respect to the death theme axis, the study was done in works by Alves, Arantes, Cortella, Kübler Ross, and Norbert Elias, among other authors also studied. After the study of those ones, an anonymous survey for public opinion was carried out, with questions that approached the themes, using the platform Google Forms as a tool, with 197 respondents, with ages equal or above 60 years old. Where the results are concerned, it was ascertained that the participants developed religious/spiritual activities, and believed in God as well; and that aging brings along a greater necessity for spiritual search, and also that faith helps in the hope for better days. The participants showed sympathy towards the neediest elderlies, and said that resilience could well be learned; that they shall get stronger within adversities, and that the historic personage that inspired them the most for overcoming difficulties was Jesus. They believed in life after death; that faith and prayer are strategies that help to overcome difficulties in facing death. Afterwards, in the last months of 2020, another opinion survey was carried out with some religions in the State of Paraíba, aiming to know whether they knew about the resilience theme or not. The responses to these studies pointed out that this universe has subjective and complex characteristics, signaling that there needs to be a more in-depth approach into the issue. However, the fact of highlighting the importance of religious/spiritual values in a multireligious and systemic way seems to contribute for resilience and to conjecture an alignment of the studied Brazilian elderly's profile: they are resilient; multireligious; environmentally activistic; believe in life after death; take part in the events in their community; wish to learn new things; and consider that religion/spirituality act successfully in the strategic support to face difficulties in life and social inequalities. Society desires that there should be no distance between it and universities. Thus, it is expected that the current study shall contribute to strengthen the relationship between the citizen and the reading about aging-related scientific texts.